Multifaceted array‐based keloidal gene expression profiling reveals specific MDFI upregulation in keloid lesions. (1st October 2021) - Asai, M.; Koike, Y.; Kuwatsuka, Y.; Yagi, Y.; Kashiyama, K.; Tanaka, K.; Mishima, H.; Yoshiura, K.; Utani, A.; Murota, H.
Summary: Background: Keloid lesions are characterized by mesenchymal cell proliferation and excessive extracellular matrix deposition. Previous microarray analyses have been performed to investigate the mechanism of keloid development. However, the molecular pathology that contributes to keloid development remains obscure. Aim: To explore the underlying essential molecules of keloids using microarrays. Methods: We performed microarray analyses of keloid and nonlesional skin tissues both in vivo and in vitro . Gene expression levels were compared between tissues and cells. Quantitative reverse transcription (qRT)‐PCR and immunohistochemical staining were used to determine the expression levels of molecules of interest in keloid tissues. Results: Several common molecules were upregulated in both keloid tissues and keloid‐lesional fibroblasts. PTPRD and NTM were upregulated both in vivo and in vitro . The genes MDFI and ITGA4 were located at the centre of the gene coexpression network analysis using keloid tissues. qRT‐PCR revealed significant expression levels of PTPRD and MDFI in keloid tissues. Immunopathological staining revealed that MDFI‐positive cells, which have fibroblast characteristics, were located in the keloid‐associated lymphoid tissue (KALT) portion of the keloid tissue. Conclusion: Our gene expression profiles of keloids could distinguish the difference between lesional tissue and cultured lesional fibroblasts, and MDFI was found to be commonly expressed in both tissues and cells. Thus, MDFI ‐positive cells, which were located in the KALT, may play an important role in keloid pathogenesis and thus might be useful for in vitro keloid studies.